Research methods : a process of inquiry - Graziano, Anthony M. , 1932-; Raulin, Michael L. (Pearson, 2013)
This comprehensive text explores the entire range of research methodologies in psychology, using a carefully constructed programmatic approach to introduce topics and systematically build on the earlier presentations